Kualitas Pelayanan Pendidikan di TK Aisyiyah Kota Sukabumi: Strategi Pendekatan Metode Service Quality - Lastriyani, Indri; Lidiawati; Sauri, R.Supyan; Wasliman, Iim (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2023)
This study delves into the satisfaction level of parents regarding the educational services provided by Aisyoyah Kindergarten in Sukabumi City. There are five dimensions of educational services: Tangibles (Physical Evidence), Reliability, Responsiveness, Assurance, and Empathy. The research addresses two main questions: (1) To what extent are parents satisfied with the educational services at Aisyoyah Kindergarten in Sukabumi City? (2) How does Aisyoyah Kindergarten in Sukabumi City enhance strategies to satisfy parents regarding educational services? This is a descriptive study employing a quantitative approach. The research subjects include parents of students from classes A and B at Aisyoyah Kindergarten in Sukabumi City, with a sample size of 36 from a total population of 61 students. Data collection techniques encompassed questionnaires, documentation, and interviews. Based on the research findings, it can be concluded that the satisfaction level of parents concerning educational services, covering the dimensions of Tangibles or Physical Evidence, Reliability, and Assurance, at Aisyoyah Kindergarten in Sukabumi City stands at 75%, falling under the category of